Urgent Implementation of Regulatory Technology and Supervisory Technology in the Financial Technology Industry - Hapsari , Recca Ayu; Resmi, Mahkota Djati Sinto; Safitri, Melisa (Arena Hukum, 2024)
Financial technology represents a significant innovation in Indonesia’s financial sector, encompassing regulation, practice, and oversight. While fintech has expanded rapidly, the surge in users has led to more complex products. This complexity increases the susceptibility of fintech to abuses, heightening risks of fraud, money laundering, and predatory lending. To mitigate these risks, the implementation of financial technology must be rigorously regulated and supervised, supported by advancements in regulatory and supervisory technology. This study aims to conduct a juridical analysis of regulatory and supervisory technology in the financial technology industry, exploring how these technologies are applied to enhance compliance and oversight. This study uses empirical methods with a qualitative-descriptive analysis approach and a socio-legal approach. The study results found that regulatory technology and supervisory technology are regulated in Articles 19 and 22 of the Financial Services Authority Regulation Number 13/POJK.02/2018 concerning Digital Financial Innovation in the Financial Services Sector. Financial technology operators carry out regulatory technology implementation with five basic regulatory technology implementation programs, namely e-KYC, e-reporting, fraud detection, regulatory compliance, and risk management, as well as the application of supervisory technology carried out by regulators with five basic programs for implementing supervisory technology, namely in the form of data analytics, e-reporting, tax reporting mining, customer support technology, and e-licensing.